Reconciliation without justice: the state and the invalidation of victimhood in post-colonial Zimbabwe, 1980–2017 - Mashingaidze, Terence M. (Brill Academic Publishers, 2022)
This article calls for the location of victimhood rather than political convenience at the centre of Zimbabwe’s peace-building matrix. From the attainment of independence in 1980 to the military assisted end of President Robert Mugabe’s rule in November 2017, Zimbabwe’s episodic cycles of violence were concluded through elite bargained amnesty ordinances, state mediated reconciliation pronouncements and clemency orders that unconditionally benefitted perpetrators at the expense of victims. The forgive-and-forget ethic central to these routine and fractional peace building measures, I argue, not only disregarded the rule of law but negated victimhood and rendered justice divisible. Victims of politically motivated violence could not secure redress through the courts of law against amnestied perpetrators as this would amount to double jeopardy. The government withheld prosecutorial justice against perpetrators and disregarded reparations for victims. Within the national legislative framework ordinary legislators could not move motions compelling the government to compensate survivors of violence because only the vice-presidents and ministers could move motions that had the consequence of either depleting state revenues or causing the imposition of additional taxes on citizens. Considering that ministers who had the prerogative to move such motions served in cabinet at the behest of their intractable president they could hardly embarrass or contradict their principal. Essentially, the Robert Mugabe led Zimbabwean government established legal firewalls for perpetrators of politically motivated violence which ipso facto invalidated the quest for justice by victims of the country’s ever recurring cycles of violence. This authoritarian legalism disregarded victimhood and emboldened human rights violators.